2016
DOI: 10.21608/esj.2016.3986
|View full text |Cite
|
Sign up to set email alerts
|

Full-Endoscopic Soft Tissue Approach for Lumbar Disc Herniation

Abstract: Background Data: Open lumbar microdiscectomy has been considered the gold standard in the management of lumbar disc herniation (LDH) because of its favorable outcomes in long-term follow up. Nowadays, minimally invasive discectomy is gaining recognition due to its advantages. The advantages endoscopic lumbar discectomy includes clear visualization, less injury to the paraspinal muscle, protection of spinal stiffness and dynamic structure better cosmetic effect, and less postoperative symptoms and open surgeryr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…1,31 In 1977, Foley and Smith 12 first introduced the microendoscopic discectomy for lumbar intervertebral disc herniation. Nonetheless, remarkable technical evolution ensues paradigm shift in indications for microendoscopic spine surgery from disc slippage into lumbar spinal canal stenosis where decompressive spinal laminotomy has been devised as a conjunction between unilateral laminotomy and microendoscopic discectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,31 In 1977, Foley and Smith 12 first introduced the microendoscopic discectomy for lumbar intervertebral disc herniation. Nonetheless, remarkable technical evolution ensues paradigm shift in indications for microendoscopic spine surgery from disc slippage into lumbar spinal canal stenosis where decompressive spinal laminotomy has been devised as a conjunction between unilateral laminotomy and microendoscopic discectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted upon large cohort reaching 583 patients however it has three main limitations: (1) No control cohort of wide laminectomy; the gold standard technique for LCS management (2) other indications for MEDL inclusive of degenerative spondylolisthesis and scoliosis were excluded (3) Follow-up period was too short which has a significant impact upon clinical outcome, complication rate as well as precise risk of post-operative instability.…”
mentioning
confidence: 99%
“…2,29,30,34,42 Only few series 35,37,41 have directly compared open laminotomy with open laminectomy. Several studies 1,2,20,22,31,33,38 have shown benefits of spinal endoscopic fenestration, including decreased blood loss, shorter operative time, shorter hospital duration, decreased postoperative narcotic requirement, decreased rate of infection and CSF leak, and a decrease in time required for returning to work.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgery can be classified into microscopic, endoscopic and percutaneous procedures. 2,20 Nowadays, "Minimally Invasive Surgery" is a trend setting catchword, but in the seventies the application of microsurgical techniques derived from intracranial procedures to the lumbar spine was a breakthrough. 1 In 1997 Smith and Foley introduced the microendoscopic discectomy (MED) system, which allowed spinal surgeons to decompress a symptomatic lumbar nerve root reliably.…”
Section: Introductionmentioning
confidence: 99%